THE DYNAMIC OF THE AVANT-GARDE GROUP AROUND ‟UNU” LITERARY MAGAZINE - Emilia FAUR (Studia Universitatis Babeș-Bolyai. Philosophia, 2017)
The Dynamic of the Avant-garde Group around Unu Literary Magazine. Going through the history of Unu literary magazine, the article describes the dynamic relationship of its group members taking into account their artistic and cultural-political stance. The evolution of the group towards a radical approach and its ideology is grasped on taking on two study cases: the Contimporanul– unu debate and the relationship carried among the group’s members. The purpose of the study is to point to how the group’s ideology had an impact on its progress and dynamic constitution. Moreover, finally, the study indicates how the internal and exterior pressure led to the magazine’s dissolution.